you distribute the 2 to everything in the paranthises and you goet -2z+-2/-14=-3z, then you add the -2z to both sides and you get -2/-14=-z, then you do -2/-14 which is -1/7=-z, then multiply both sides by -1 to get -(-1/7)=-(-z) which then gives you z=1/7
Ask.com is not a place where we do hw for other people... For this problem, you need to be familiar with PEMDAS and the properties. I suggest you go to pwcgov.org and go to their free online hw help section!!
I think you are saying -2(z-(1/7))=-3z if this is the case, first get rid of the parenthesis to give -2*z -2*-(1/7)=-3z to give -2Z+2/7=-3Z add 2Z to both sides to give 2/7=Z Does this make sense? Any questions?